Experimental validation of a bidirectional three-level dc-dc converter for on-board or off-board EV battery chargers - Monteiro, Vítor Duarte Fernandes (2019)
This paper presents a bidirectional three-level (B3L) dc dc converter for electric mobility applications, namely for EV battery chargers (structures of on board or off board). As shown throughout the paper, the B3L dc dc converter is only part of the on board or off board chargers, and may also be framed in galvanic isolated or non isolated electrical systems. As main differentiating factor, according to the output voltage value, it can operate with three levels, allowing to reduce the voltage applied to each switching device. Besides, it operates with the output controlled current with a frequency that is double of the switching frequency of each device. Taking into account the advantages of the B3L dc dc converter, a comparison with a conventional converter is established. The adopted PWM strategy is defined according to the current control technique. The experimental validation is performed using two prototypes: an on board charger and an off board charger. The obtained results allow verifying the claimed innovative characteristics and advantages of the B3L dc dc converter.